Neighborhood Crime Undermines Parenting : Violence in the Vicinity of Households as a Predictor of Aggressive Discipline (2017)
Child discipline is a central component of parent-child interactions. Evidence suggests corporal discipline impairs children's development and compromises their future chances, especially since it is more frequently used against at-risk children. Using geocoded data, this study analyzes the relation between crimes in the vicinity of households in four major urban municipalities of Colombia and a particularly violent corporal discipline practice: hitting children with objects. Results indicate that exposure to violent crimes, such as homicides and personal injuries, predicts a higher probability of hitting children with objects, even after controlling for a set of individual, family and neighborhood characteristics. These findings suggest households' walls are permeable, and outside threats may interfere with families' dynamics and well-being. Future directions and implications are discussed